Effects of workplace bullying on Chinese children's health, behaviours and school adjustment via parenting: study protocol for a longitudinal study - Catalina Sau Man Ng (BMC, 2019)
Abstract Background Bullying in the workplace is a serious public health issue. As a chronic work stress, workplace bullying places the victims' physical and mental health at risk which, in extreme cases, may lead to suicidal ideation. The high prevalence rate of workplace bullying has been reported and documented globally. However, a major limitation of the existing literature is that studies essentially focus on the consequences of workplace bullying on victims, including the psychological, physiological and socioeconomic impacts, and on the factors causing workplace bullying, but research on the impact of workplace bullying on the victims' families is lacking. It is however evident that the consequences of workplace bullying have a spillover effect on the victims' family members. Since many victims have children and given that children are particularly vulnerable to a negative family environment, examining the impacts of the type of parental stress induced by workplace bullying on children's health including physical and psychological health (depression and self-esteem), externalizing problem behaviors (aggression, lying, disrespect) and school adjustment (academic performance and school conduct) is urgently needed. The overall aim of this study is to examine how health, externalizing problem behaviors and school adjustment of children whose parents are victims of workplace bullying may be associated with the impact that workplace bullying has on parenting practices. Methods It is a longitudinal study. Quantitative data will be collected from multi-informants, including currently employed Chinese parents, their children aged between 6 and 12 years old, and their class teachers at two time points, separated by a 1-year interval. One primary school will be recruited from each district of Hong Kong including participants with different socioeconomic backgrounds. At least 837 dyads (parents and children) from 18 primary schools will join the study. Discussion Workplace bullying not only affects victims but can also be harmful to their families as it alters the victims temper in the family environment. Results will be informative for the government and corporations to make concerted efforts and find strategies to prevent workplace bullying and to heighten the awareness of the importance of promoting safe and respectful workplaces for workers.